Pelatihan Teater dengan Metode Role Play untuk Meningkatkan Kepercayaan Diri Siswa di Kabupaten Takalar - Andi Baetal Muqaddas; Irfan; Satriadi; Muhammad Zia Ulhaq; Yati Bt. Samsudin (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The low level of self-confidence among students remains a common issue found in many schools, including those in Takalar Regency, South Sulawesi. A lack of courage to perform, limited initiative, and awkwardness in social interactions are problems that negatively affect the learning process and academic achievement. This community service program aims to enhance students’ self-confidence through theater training using the role-play method. The implementation of the program consisted of several stages, including socialization, delivery of basic theater material, role-play technique training, performance mentoring, and evaluation. The results showed an increase in students’ courage in speaking, performing in public, collaborating, and expressing ideas. The program also opened opportunities for the establishment of a theater extracurricular activity as a sustainable platform for developing students’ character.